Violent Conflict in Contemporary Europe: Specifying the Relationship Between War Exposure and Interpersonal Violence in a War-Weary Country - Timmer, Anastasiia (The British journal of criminology, 2023)
This study uses survey data from multi-stage stratified random samples of adults from two large Ukrainian cities to examine and specify associations between war exposure and the likelihood of committing violent acts against another person. Findings from regression models reveal that both direct and vicarious war exposure predict projected interpersonal violence by civilians, and mediation analyses show that daily strains and, in some instances, negative affect serve as links in the relationship between vicarious war exposure and the likelihood of violent behaviour. Daily strains also emerge as a significant and robust moderator of this relationship. The study demonstrates dangerous effects of war-related events on civilians and highlights the need for interventions aimed at reducing violence in war-weary countries around the world.